Occupational therapy Approaches for sensory integration in autism spectrum disorder: scoping review - Noura Sadeki; sirine hadjer Zaabta (Journal of Science and Knowledge Horizons, 2025)
Sensory treatment for children on the autism spectrum is one of the most prominent thorny topics that studies in all its forms have dealt with. Reliance was placed on presenting the latest theories that dealt with this topic, and what therapists have provided from 2014 to 2023 for children with their various types. The work aims to examine the sensory patterns and processing systems in children, and was completed. Treatment through a literary review of relevant literature from 2014 to 2023 through a database of databases published online in this field (PubMed, Eric, Web of Science, Google Scholar, and Scopus). (16) studies were extracted from Among them is one study in Arabic that was translated into English.    Following the submission, the inclusion criteria for 16 studies were analysed. The search was conducted by combining the keywords (autism), (sensory processing) (sensory processing disorder), and the results showed that children with autism show atypical sensory processing more than children who typically develop. natural.